Conversion efficiency in silicon solar cells with spatially non-uniform doping - Sachenko, A.V.; Prima, N.A.; Gorban, A.P. (Semiconductor Physics Quantum Electronics & Optoelectronics, 1999)
The conversion efficiency of diffusion-type silicon solar cells, η, is studied theoretically in assumption of different doping levels existing under collection grid contacts and within the inter-contact spacing. It is shown that at high under-contact doping levels and at relatively low inter-contact doping ones the conversion efficiency increases as compared to uniform doping case. The dependence of η on Shockley-Reed-Hall carrier lifetimes both in the base and in the top-surface n⁺-layer as well as on the depth of p-n-junction and the shape of electron concentration profile, N(x), in the n⁺-region is analysed.